2012
DOI: 10.1002/ptr.4660
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antimycobacterial Lignans and Flavonoids from Larrea tridentata

Abstract: Three lignans and four flavonoids were isolated and characterized from Larrea tridentata and compounds were tested against 16 bacterial species/strains. Results showed that: dihydroguaiaretic acid (1) had activity towards methicillin resistant (MR) Staphylococcus aureus (minimum inhibitory concentration (MIC) 50 µg/mL) and multidrug-resistant (MDR) strains of Mycobacterium tuberculosis (MIC 12.5-50 µg/mL); 4-epi-larreatricin (2) was active against Enterobacter cloacae (MIC 12.5 µg/mL), as well as sensitive (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 12 publications
0
54
0
Order By: Relevance
“…48) This result could provide a pharmacological basis to inhibit PRRSV replication. 27) In addition, many other plant-derived substances from TMPs such as Murraya koenigii, Erythrina caffra, Corydalis saxicola, Larrea tridentate, Holarrhena antidysenterica, and Melampyrum arvense exerted antiviral, 49,50) antibacterial, 51,52) and antiprotozoal 53,54) activities.…”
Section: Major Pharmacological Activitiesmentioning
confidence: 99%
“…48) This result could provide a pharmacological basis to inhibit PRRSV replication. 27) In addition, many other plant-derived substances from TMPs such as Murraya koenigii, Erythrina caffra, Corydalis saxicola, Larrea tridentate, Holarrhena antidysenterica, and Melampyrum arvense exerted antiviral, 49,50) antibacterial, 51,52) and antiprotozoal 53,54) activities.…”
Section: Major Pharmacological Activitiesmentioning
confidence: 99%
“…In Mexico, Larrea tridentata Coville., Zygophyllaceae, has been used as a traditional medicine against respiratory infections and tuberculosis, and its antimycobacterial activity was confirmed using the chloroform extract. In 2012, Favela-Hernández et al reported 5,4′-dihydroxy-3,7,8,3′-tetramethoxyflavone (43) and 5,4′-dihydroxy-3,7,8-trimethoxyflavone (44) from this plant as having activity against both sensitive and MDR forms with MICs of 25 and 25-50 µg/mL, respectively [28]. Limnophila geoffrayi Bon., Scrophulariaceae, a common ingredient in northeastern Thailand curry, is an antipyretic, expectorant, and a lactogogue.…”
mentioning
confidence: 99%
“…Adhatoda vasica Ness., Acanthaceae, which is used in the treatment of colds, cough, and other respiratory disorders, contains antimicrobial compounds. Alkaloids present in the hexane extract like vasicine acetate (1) and 2-acetyl ben- [21] dihydroguaiaretic acid (50 µg/mL) (12.5-50 µg/mL) [28] pisonin B (25 µg/mL) [32] falcarindiol (26.7 µg/mL) [65] 2′-nortiliacorinine and tiliacorine (3.1 µg/mL) (3.1 µg/mL) [12] pinocembrin (3.5 µg/mL) [18] (E)-3,2′,4′-trihydroxy-3′-methoxychalcone (174.8 µM) [21] 4-epi-larreatricin (50 µg/mL) (25 µg/mL) [28] [33] licarin A (25 µg/mL) (3.12-12.5 µg/mL) [42] linoleic acid and oleic acid (100 µg/mL) (100 µg/mL) [46] 1,3 dimethoxy-2-methyl-5-pentyl benzene (≤ 2.5 µg/mL) [66] 13′-bromo-tiliacorinine (3.1-6.2 µg/mL) (1.5-3.1 µg/mL) [12] kanzanol C, 4-hydroxylonchocarpin, stipulin, and amentoflavone (9.76 -> 39.06 µg/mL) [19] aminoacetate derivative of diospyrin (> 10 -≤ 50 µg/mL) (> 10 -≤ 50 µg/mL) [34] licarin B (50 µg/mL) (12.5-50 µg/mL) [42] undecanal (100 µg/mL) (50-200 µg/mL) [46] 3-methoxy-2-methyl-5-pentyl phenol (≤ 2.58 µg/mL) [66] Mauritine M (IC 50 − 72.8 µM) [13] genistein (35 µg/ml) [20] diospyrin (100 µg/mL) (100 µg/mL) [34] eupomatenoid-7…”
mentioning
confidence: 99%
See 2 more Smart Citations